Whistle : a novel - Barclay, Linwood (William Morrow, an imprint of HarperCollinsPublishers, 2025)
A woman and her young son move to a small town looking for a fresh start, only to be haunted by disturbing events and strange visions when they find a mysterious train set in a storage shed.